2017
DOI: 10.1007/s10455-017-9575-z
|View full text |Cite
|
Sign up to set email alerts
|

The index of Callias-type operators with Atiyah–Patodi–Singer boundary conditions

Abstract: Abstract. We compute the index of a Callias-type operator with APS boundary condition on a manifold with compact boundary in terms of combination of indexes of induced operators on a compact hypersurface. Our result generalizes the classical Callias-type index theorem to manifolds with compact boundary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Bär and Ballmann, [6,7], showed that an elliptic boundary value problem for a Callias-type operator on a complete manifold with compact boundary is Fredholm and studied its index. P. Shi, [37], proved a version of the Callias-type index theorem for the Atiyah-Patodi-Singer (APS) boundary value problem for Callias-type operators on a complete manifold with compact boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Bär and Ballmann, [6,7], showed that an elliptic boundary value problem for a Callias-type operator on a complete manifold with compact boundary is Fredholm and studied its index. P. Shi, [37], proved a version of the Callias-type index theorem for the Atiyah-Patodi-Singer (APS) boundary value problem for Callias-type operators on a complete manifold with compact boundary.…”
Section: Introductionmentioning
confidence: 99%
“…P. Shi, [37], proved a version of the Callias-type index theorem for the APS boundary value problem for Callias-type operators on a complete odd-dimensional manifold with compact boundary.…”
Section: Introductionmentioning
confidence: 99%
“…On noncompact manifolds, APS index theory of Callias-type Dirac operators was developed by Braverman and Shi [14,15,55,56]. Braverman also obtained a result for Callias-type operators on noncompact Lorentzian manifolds with boundary [12], which was proved in the compact case by Bär-Strohmaier [6].…”
mentioning
confidence: 99%